Comparing alcohol taxation throughout the European Union. (30th May 2019) - Angus, Colin; Holmes, John; Meier, Petra S.
Abstract: Background and Aims: The World Health Organization recommends increasing alcohol taxes as a 'best‐buy' approach to reducing alcohol consumption and improving population health. Alcohol may be taxed based on sales value, product volume or alcohol content; however, duty structures and rates vary, both among countries and between beverage types. From a public health perspective, the best duty structure links taxation level to alcohol content, keeps pace with inflation and avoids substantial disparities between different beverage types. This data note compares current alcohol duty structures and levels throughout the 28 European Union (EU) Member States and how these vary by alcohol content, and also considers implications for public health. Design and Setting: Descriptive analysis using administrative data, European Union, July 2018. Measurements: Beverage‐specific alcohol duty rates per UK alcohol unit (8 g ethanol) in pounds sterling at a range of different alcoholic strengths. Findings: Only 50% of Member States levy any duty on wine and several levy duty on spirits and beer at or close to the EU minimum level. There is at least a 10‐fold difference in the effective duty rate per unit between the highest‐ and lowest‐duty countries for each beverage type. Duty rates for beer and spirits stay constant with strength in the majority of countries, while rates for wine and cider generally fall as strength increases. Duty rates are generally higher for spirits than other beverage types and are generally lowest in eastern Europe and highest in Finland, Sweden, Ireland and the United Kingdom. Conclusions: Different European Union countries enact very different alcohol taxation policies, despite a partially restrictive legal framework. There is only limited evidence that alcohol duties are designed to minimize public health harms by ensuring that drinks containing more alcohol are taxed at higher rates. Instead, tax rates appear to reflect national alcohol production and consumption patterns.